Supporting multiple birth families: Perceptions and experiences of health visitors. Issue 1 (10th November 2021) - Turville, Nathalie; Alamad, Lara; Denton, Jane; Cook, Robert; Harvey, Merryl
Abstract: Objective: To explore the current practice and perceptions of health visitors in supporting multiple birth families. Design and sample: Practicing health visitors across the United Kingdom were invited to complete a cross‐sectional, descriptive, online survey. The questionnaire covered multiple birth caseload, education received about multiples and the experience of working with families. Two‐hundred and ninety health visitors completed the questionnaire. Descriptive and inferential statistics were used for analysis of the quantitative components and thematic analysis for the qualitative data. Results: Most health visitors had twins on their current workload. Most health visitors had not received any specific training or continuing professional development regarding the needs of multiple birth families. Supporting the families within the confines of reduced time and increased workload was challenging. Daily tasks of caring for multiples were the main areas that health visitors and parents wanted more information about. Conclusions: In the United Kingdom, health visitors are uniquely positioned to support multiple birth families, in particular during the more challenging early years. However, the findings of this study suggest that many health visitors are aware that the care and support that they are able to provide multiple birth families falls short of meeting their needs